Frailty Is Associated with an Increased Risk of Complications and Need for Repeat Procedures after Sling Surgery in Older Adults. Issue 6 (21st June 2022) - Van Kuiken, Michelle E.; Zhao, Shoujun; Covinsky, Kenneth; Boscardin, John; Finlayson, Emily; Suskind, Anne M.
Abstract : Purpose: Sling surgery is the gold standard treatment for stress urinary incontinence in women. While data support the use of sling surgery in younger and middle-aged women, outcomes in older, frail women are largely unknown. Materials and Methods: Data were examined for all Medicare beneficiaries ≥65 years old who underwent sling surgery with or without concomitant prolapse repair from 2014 to 2016. Beneficiaries were stratified using the Claims-Based Frailty Index (CFI) into 4 categories: not frail (CFI <0.15), prefrail (0.15 ≤CFI <0.25), mildly frail (0.25 ≤CFI <0.35) and moderately to severely frail (CFI ≥0.35). Outcomes included rates and relative risk of 30-day complications, 1-year mortality and repeat procedures for persistent incontinence or obstructed voiding at 1 year. Results: A total of 54, 112 women underwent sling surgery during the study period, 5.2% of whom were mildly to moderately to severely frail. Compared to the not frail group, moderately to severely frail beneficiaries demonstrated an increased adjusted relative risk (aRR) of 30-day complications (56.5%; aRR 2.5, 95% CI: 2.2–2.9) and 1-year mortality (10.5%; aRR 6.7, 95% CI: 4.0–11.2). Additionally, there were higher rates of repeat procedures in mildly to severely frail beneficiaries (6.6%; aRR 1.4, 95% CI: 1.2–1.6) compared to beneficiaries who were not frail. Conclusions: As frailty increased, there was an increased relative risk of 30-day complications, 1-year mortality and need for repeat procedures for persistent incontinence or obstructed voiding at 1 year. While there were fewer sling surgeries in performed frail women, the observed increase in complication rates was significant. Frailty should be strongly considered before pursuing sling surgery in older women.